The Navigation and Trade Agreement of 1718 and the Ottoman Orthodox Merchants in Civil Croatia and Parts of the Military Border - Petrić, Hrvoje (Array, 2011)
Tekst prikazuje kako se mir 1718. odrazio na ekonomiju dijela pograničnog područja.